Immune-mediated inflammatory diseases and leukocyte telomere length: A Mendelian randomization study - Liu, Meiling; Luo, Ping; Liu, Lihua; Wei, Xianping; Bai, Xue; Li, Jicui; Wu, Linlin; Luo, Manyu (Frontiers in Genetics, 2023)
Objective: To elucidate the potential causality of leukocyte telomere length (LTL) with immune-mediated inflammatory diseases (IMIDs), we conducted a Mendelian randomization (MR) study. Methods: The genetically predicted causation between LTL and IMIDs was evaluated using a two-sample MR method. We here analyzed 16 major IMIDs including systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD), ulcerative colitis (UC), Crohn’s disease (CD), ankylosing spondylitis (AS), sicca syndrome (SS), rheumatoid arthritis (RA), type 1 Diabetes (T1D), primary sclerosing cholangitis (PSC), idiopathic pulmonary fibrosis (IPF), atopic dermatitis (AD), sarcoidosis, hypothyroidism, hyperthyroidism, psoriasis, childhood asthma. The random-effects inverse-variance weighted (IVW) method was performed as the main analytical approach in MR. Various sensitivity analyses, including MR-Egger, Mendelian Randomization robust adjusted profile score (MR-RAPS), weighted median, MR pleiotropy residual sum and outlier methods (MR-PRESSO), weighted mode, radial plot, and radial regression, were used to guarantee the robustness of the results and detect horizontal pleiotropy. Cochran's Q value was calculated to check for heterogeneity, and MR steiger is used to test the causal direction.Results: The MR results indicated significant inverse associations of LTL with risks of psoriasis (OR:0.77, 95% CI: 0.66-0.89, P=3.66x10-4), SS (OR:0.75, CI: 0.58-0.98, P=0.03), RA (OR:0.77, 95% CI: 0.68-0.88, P=9.85x10-5), hypothyroidism (OR:0.84 95% CI: 0.78-0.91, P=7,08x10-6), hyperthyroidism (OR:0.60, 95% CI: 0.44-0.83, P=1.90x10-3), sarcoidosis (OR:0.67, 95% CI: 0.54-0.83, P=2.60x10-4), and IPF (OR: 0.41, 95% CI: 0.29-0.58, P=4.11x10-7) in the FinnGen study. We observed longer LTL was associated with an increased risk of AS susceptibility (OR: 1.51, 95% CI: 1.18-1.94, P=9.66x10-4). The results of the IVW method showed no causal relationship between TL and SLE (OR:0.92, 95% CI: 0.62-1.38, P=0.69) in FinnGen, whereas it showed a significantly positive correlation between LTL and SLE in another larger GWAS (OR:1.87, 95% CI: 1.37-2.54, P=8.01x10-5). Conclusion: Our findings reveal that abnormal LTL has the potential to increase the risk of IMIDs. Therefore, it could be treated as a predictor and may provide new potential treatment targets for IMIDs. However, the change of LTL may not be the direct cause of IMIDs. Further studies should aim at the pathogenic mechanism or potential protective effects of LTL in IMIDs.